Comparison of inverters' performance as active power filters with unified constant-frequency integration control - Lim, Pei Yi; Ahmad Azli, Naziha (Penerbit UTM Press, 2007)

(untitled)
Active Power Filter (APF) is well known for its capability of compensating current harmonics in power lines. Vast varieties of APF configurations were proposed for the past few decades, but not many papers consider the expansion capability of APFs. This article presents the comparison of performance for the conventional single level H–bridge inverter and Modular Structured Multilevel Inverter where both are controlled by Unified Constant-Frequency Integration (UCI) control scheme. The latter inverter structure is more flexible to be expanded to suit higher power application. Characteristics of each topology are discussed and the simulation results based on MATLAB/SIMULINK are presented.